Anxiety, Motivation, and Competence in Mathematics and Reading for Children With and Without Learning Difficulties - Pollack, Courtney; Wilmot, Dayna; Centanni, Tracy M.; Halverson, Kelly; Frosch, Isabelle; D'Mello, Anila M.; Romeo, Rachel R.; Imhof, Andrea; Capella, Jimmy; Wade, Karolina; Al Dahhan, Noor Z.; Gabrieli, John D. E.; et al. (Frontiers in Psychology, 2021)
Knowledge of the relations among learners’ socio-emotional characteristics and competencies as they engage in mathematics and reading is limited, especially for children with academic difficulties. This study examined the relations between anxiety, motivation, and competence in mathematics and reading, within and across domains, in an academically-diverse set of 8–13-year-old learners (n = 146). To measure anxiety and motivation across domains, we paired existing measures of math anxiety and reading motivation with researcher-developed analogues for reading anxiety and math motivation. Participants completed standardized assessments of mathematics and reading, anxiety and motivation surveys for math and reading, and a measure of nonverbal cognitive ability. Results showed high internal consistency for all anxiety and motivation scales (Cronbach’s alpha = 0.76-0.91). Pearson correlations showed that within and across domains, participants with higher competence had lower anxiety and higher motivation. Higher anxiety was also associated with lower motivation. Regression analyses showed that for both math and reading, within-domain motivation was a stronger predictor of competence than anxiety. There was a unidirectional across-domain relation: socio-emotional characteristics for reading predicted math competence, after accounting for nonverbal cognitive ability, age, gender, and within-domain anxiety and motivation. Results contribute to knowledge of the socio-emotional characteristics of children with and without learning difficulties in association with reading and math activities. Implications of a unidirectional socio-emotional link between the two domains can advance research and theory of the relations among socio-emotional characteristics and competence for academically-diverse learners.